2002
DOI: 10.1089/154065802761001329
|View full text |Cite
|
Sign up to set email alerts
|

A High Throughput Screening Assay to Screen for CYP2E1 Metabolism and Inhibition Using a Fluorogenic Vivid® P450 Substrate

Abstract: Large-scale screening of multiple compound libraries and combinatorial libraries for pharmacological activity is one of the novel approaches of the modern drug discovery process. The application of isozyme-specific high-throughput screening (HTS) assays for characterizing the interactions of potential drug candidates with major human drug-metabolizing cytochrome p450 enzymes (p450s) is newly becoming an essential part of this process. Fluorescence-based HTS assays have been successfully employed for in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…Although microsomal assays are commonly used to evaluate the activity of P450 enzymes, fluorescent methods for determining P450 activity allow for high-throughput screening and more reproducible results [21][22][23][24][25] . Bell et al found that nearly 75% of marketed drugs yielded acceptable correlations between fluorogenic and HLM+LC-MS/MS assays for CYPs 3A4, 2D6, and 2C9, which supports the use of fluorogenic assays for rapid early risk binning based on IC 50 values [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Although microsomal assays are commonly used to evaluate the activity of P450 enzymes, fluorescent methods for determining P450 activity allow for high-throughput screening and more reproducible results [21][22][23][24][25] . Bell et al found that nearly 75% of marketed drugs yielded acceptable correlations between fluorogenic and HLM+LC-MS/MS assays for CYPs 3A4, 2D6, and 2C9, which supports the use of fluorogenic assays for rapid early risk binning based on IC 50 values [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the induction potency for compounds examined here varied significantly, most were consistent with previously reported data allowing discrimination between potent, moderate, and weak CYP3A4 inducers. For example, maximal levels of induction (up to 35-fold) were obtained for rifampicin, a previously reported prototypical CYP3A4 inducer of high potency, 14 whereas incubation in the presence of paclitaxel, a previously reported weak CYP3A inducer, 15 resulted in only a 2-fold induction of luciferase reporter gene activity.…”
Section: Identification Of Cyp3a4 Inducers In the Dpx-2 Cell Linementioning
confidence: 91%
“…Burke and Mayer (1974) first used the P450-catalyzed O-dealkylation of alkoxyresorufins to examine the induction of hepatic P450 activity by fluorescence. Since then, various O-alkyl derivatives of resorufin, fluorescein, 7-hydroxycoumarins, and 6-hydroxyquinolines have been examined as substrates, and some have been commercialized for use in P450-mediated drug interaction studies (Clarke, 1999;Stresser et al, 2000;Bapiro et al, 2001;Crespi and Stresser, 2001;Miller et al, 2001;Marks et al, 2002). The complex kinetic patterns known for P450 enzymes with several probe substrates and inhibitors (Tang and Stearns, 2001;Hutzler, 2002) suggested that similar complexity is to be expected with fluorogenic substrates.…”
mentioning
confidence: 99%